Technique for assessment of voltage stability in Ill-conditioned radial distribution network - Moghavvemi, M.; Faruque, M.O. (IEEE, Piscataway, NJ, United States, 2001)
A technique is proposed in this letter to study voltage collapse situation in a radial distribution network. The radial distribution network has been reduced to a single line equivalent circuit and then represented through a π network. A stability index is developed that indicates the severity of the loading situation of the system. The index can have a maximum value of one (1.00) when the system is at the point of collapse and a minimum value of zero (0) when there is no load in the system. Voltage collapse can be assessed based on the value of the developed index. If the system yields a value exceeding its maximum limit of stability index (1.00) it indicates voltage collapse situation. The proposed technique is tested on a practical system of 12-bus radial system (main feeders only) and on a 27-bus radial distribution system with laterals. The results obtained are encouraging and indicate that the technique has the potential to be used as a tool for system monitoring and future load planning.